Leaks detection in stainless steel kegs via ESPI. (November 2018) - Pagliarulo, V.; Bianco, V.; Memmolo, P.; Distante, C.; Ruggiero, B.; Ferraro, P.
Highlights: The use of ESPI to evaluate the presence of losses in stainless steel kegs is proposed. The study is applied to different kegs. The approach allows to identify the losses in a fast way. Different algorithms are proposed to make the process semi-automatic. This method could be considered for industrial applications. Abstract: Integrity assessment of kegs is necessary to preserve the quality of the content stored and, consequently, human health. Here we show that inspection optical technique based on ESPI can be adopted successfully for assessing fully integrity of stainless steel keg. In particular two kegs, the first pre-finished and the second with a known leak, are compared in order to test the possibility to employ ESPI as a non-destructive testing tool to quickly revealing the presence and to partially locate a leak in automatic way. The acquired speckle images have allowed measurements of deformations of the two kegs under a known pressure. We demonstrate that the anomaly into the fringes dynamic pattern and the corresponding phase-contrast maps clearly reveal the presence of imperfections in the welding processes. We propose different algorithms customized to automate the process of leak recognition, localization and quantification thus validating ESPI system, for the first time in our knowledge, to test the quality of the production of steel kegs through a very fast process. In particular the proposed fringes analysis is completely new and it has been designed specifically for the kegs characteristics. We think this procedure could be utilized for industrial applications with the aim to improve quality and reduce costs.